De Novo ARID1B mutations cause growth delay associated with aberrant Wnt/β–catenin signaling. Issue 5 (3rd March 2020) - Liu, Xiaomin; Hu, Guorui; Ye, Jun; Ye, Bin; Shen, Nan; Tao, Yue; Zhang, Xia; Fan, Yanjie; Liu, Huili; Zhang, Zhigang; Fang, Danfeng; Gu, Xuefan; et al.
Abstract: Haploinsufficiency of ARID1B (AT‐rich interaction domain 1B) has been involved in autism spectrum disorder, nonsyndromic and syndromic intellectual disability, and corpus callosum agenesis. Growth impairment is a major clinical feature caused by ARID1B mutations; however, the mechanistic link has not been elucidated. Here, we confirm that growth delay is a common characteristic of patients with ARID1B mutations, which may be associated with dysregulation of the Wnt/β–catenin signaling pathway. An analysis of patients harboring pathogenic variants of ARID1B revealed that nearly half had short stature and nearly all had below‐average height. Moreover, the percentage of patients with short stature increased with age. Knockdown of arid1b in zebrafish embryos markedly reduced body length and perturbed the expression of both chondrogenic and osteogenic genes including sox9a, col2a1a, runx2b, and col10a1 . Knockout of Arid1b in chondrogenic ATDC5 cells inhibited chondrocyte proliferation and differentiation. Finally, Wnt/β–catenin signaling was perturbed in Arid1b‐depleted zebrafish embryos and Arid1b knockout ATDC5 cells. These data indicate that ARID1B modulates bone growth possibly via regulation of the Wnt/β–catenin pathway, and may be an appropriate target for gene therapy in disorders of growth and development. Abstract : Growth delay is a common feature associated with ARID1B mutations. Nearly half of ARID1B patients had short stature, and nearly all had below‐average height (a). The percentage of patients with short stature increased with age (b). No differences in height distribution were observed between patients with and those without feeding difficulties or recurrent infections (c), indicating that ARID1B mutations, but not feeding difficulties or recurrent infections, primarily affect height.